One-Pot Synthesis of Magnetic Polypyrrole Nanotubes for Adsorption of Cr(VI) in Aqueous Solution - Wenjuan Zhang; Yaxian Wang; Yulong Fei; Youliang Wang; Zhaoxiong Zhang; Miao Kou; Qiancheng Feng; Sheng Wang; Xueyan Du (Advances in Materials Science and Engineering)
A novel and efficient route is proposed to fabricate Fe3O4/polypyrrole (Fe3O4/PPy) nanotubes via a one-pot process. The one-pot strategy involves the synthesis of Fe3O4/PPy nanotubes by oxidative polymerization of pyrrole (Py) monomer using Fe3+ as an oxidant in the presence of methyl orange (MO) and Fe3+ used as iron source to form Fe3O4 simultaneously in basic conditions without adding any additional iron source and oxidant. The effects of Fe3+ concentration on the morphology and adsorption capacity of the Fe3O4/PPy nanotubes were investigated. The Fe3O4/PPy nanotubes exhibit a tubular structure. Fe3O4 nanoparticles are well dispersed among the PPy nanotubes. The Fe3O4/PPy nanotubes exhibit excellent magnetic property, which make them easy to separate from wastewater by magnetic separation. The diameter of the PPy nanotubes decreased with the increase of the Fe3+ concentration. The Fe3O4/PPy nanotubes showed strong adsorption capability for Cr(VI) with the maximum adsorption capacity of about 451.45 mg·g−1, which is significantly higher than bare Fe3O4 nanoparticles. Cr(VI) was adsorbed on Fe3O4/PPy nanotubes by ion exchange and chelation, where Cr(VI) was partially reduced to Cr(III) due to the existence of −NH+ on the Fe3O4/PPy nanotubes. Furthermore, the Fe3O4/PPy nanotubes are recyclable, retaining 90% of the initial removal efficiency after 5 adsorption/desorption cycles.